2020
DOI: 10.3892/or.2020.7760
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1α inhibits p53 downstream of MDM2‑mediated autophagy and apoptosis in acute myeloid leukemia

Abstract: Enhancement of autophagy serves as a promising therapeutic strategy for cancer, including acute myeloid leukemia (AML). Casein kinase 1α (CK1α), encoded by CSNK1A1, regulates Wnt/β-catenin, p53 and other key signaling pathways, and is critically involved in tumor progression. However, the relationship and mechanism of CK1α with autophagy in AML still remain unclear. In the present study, it was found that AML patients had higher expression of CSNK1A1 mRNA than healthy donors. Furthermore, we analyzed 163 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…In this regard, it was found that CK1α inhibition led to the overexpression of autophagy genes in RAS-mutated colon cancer cell lines (Cheong et al 2015) through stabilization of transcription factor FOXO3a (regulator of autophagic flux). Recently, CK1α has been recognized as a negative regulator of oncogenic RAS-induced autophagy, further strengthening our argument that CK1αregulated autophagy can be a promising therapeutic target (Xu et al 2020). Carrino et al (2019), suggested that CK1α inhibition with the CK1α inhibitor D4476 resulted in impaired degradation of autophagosomes in multiple myeloma, which was likely related to its effect on the acidification of the lysosomes.…”
Section: Discussionsupporting
confidence: 59%
“…In this regard, it was found that CK1α inhibition led to the overexpression of autophagy genes in RAS-mutated colon cancer cell lines (Cheong et al 2015) through stabilization of transcription factor FOXO3a (regulator of autophagic flux). Recently, CK1α has been recognized as a negative regulator of oncogenic RAS-induced autophagy, further strengthening our argument that CK1αregulated autophagy can be a promising therapeutic target (Xu et al 2020). Carrino et al (2019), suggested that CK1α inhibition with the CK1α inhibitor D4476 resulted in impaired degradation of autophagosomes in multiple myeloma, which was likely related to its effect on the acidification of the lysosomes.…”
Section: Discussionsupporting
confidence: 59%
“…In MM, CK1α inhibits p53 and prevents the caspase-mediated degradation of AKT and β-catenin, promoting a cell-survival advantage [ 24 ]. In AML, knockdown or downregulation of CK1α correlates with increased expression of a p53 signature [ 21 ], and a more recent study reports that the blockage of p53 by CK1α prevents autophagy activation [ 101 ].…”
Section: Supportive Role Of Ck1α and Ck2 In The Cancer Stress Phenmentioning
confidence: 99%
“…Recently, it has been reported that, in AML, CK1α exerts an opposite role in autophagy regulation, via the inhibition of p53/MDM2-mediated autophagy. Both pharmacological and genetic inhibition of CK1α induced autophagy and apoptosis in AML cell lines and patient blast cells [ 101 ]. Thus, the influence of CK1α on autophagy may be cell type and/or disease context dependent.…”
Section: Supportive Role Of Ck1α and Ck2 In The Cancer Stress Phenmentioning
confidence: 99%
“…21 In addition, several other regulators mediate MDM2, such as CK1α, and were also observed to affect the p53 signal pathway by inhibiting MDM2-mediated autophagy and apoptosis. 23 (Figure 2).…”
Section: Arf-mdm2/4/x-p53 Axismentioning
confidence: 99%